Individual Signatures Define Canine Skin Microbiota Composition and Variability - Cuscó, Anna; Sánchez, Armand; Altet, Laura; Ferrer, Lluís; Francino, Olga (Frontiers in Veterinary Science, 2017)
Dogs present almost all their skin sites covered by hair, but canine skin disorders are more common in certain skin sites and breeds. The goal of our study is to characterize the composition and variability of the skin microbiota in healthy dogs and evaluate the effect of the breed, the skin site and the individual. We have analyzed eight skin sites of nine healthy dogs from three different breeds by massive sequencing of 16S rRNA gene V1-V2 hypervariable regions. The main phyla inhabiting the skin microbiota in healthy dogs are Proteobacteria, Firmicutes, Fusobacteria, Actinobacteria and Bacteroidetes. Our results suggest that skin microbiota composition pattern is individual-specific, with some dogs presenting an even representation of the main phyla and other dogs with only a major phylum. The individual is the main force driving skin microbiota composition and diversity rather than the skin site or the breed. The individual is explaining 45% of the distances among samples, whereas skin site explains 19% and breed 9%. Moreover, analysis of similarities suggests a strong dissimilarity among individuals (R=0.79, P=0.001) that is mainly explained by low-abundant species in each dog. Skin site also plays a role: inner pinna presents the highest diversity value, whereas perianal region presents the lowest one as well as the most differentiated microbiota composition.